Persepsi Mahasiswa Terhadap Pengunduhan Film Secara Ilegal (Studi Pada Mahasiswa Fakultas Hukum Universitas X) - Julia Putri Hasibuan, Anggi (UNES Law Review, 2023)
Copyright infringement is often a problem that is difficult to handle properly. One example of copyright problems that are often encountered and difficult to solve is the illegal downloading of films on the internet which proves the rapid development of technology. The more sites that provide this film in circulation, the more films or works are downloaded for free, which is detrimental to the publisher of the work. The illegal accusation in Indonesia has increased along with the times, 63% of internet users in Indonesia who access illegal film sites and in the Hootsuite data, the most internet users are students. As a result of the rampant downloads on this illegal site, it has led to students' perceptions of downloading movies illegally on the internet. This study aims to determine the perceptions of criminal law students towards illegal downloading. This study used a quantitative descriptive approach with a sample size of 50 criminal law students. This study aims to show that students of criminal law know that copyright law and illegal downloading is a violation of copyright tend to agree, but students do not show good action to prevent illegal downloading. Motivation in committing copyright infringement is on his own will and economic factors. As for the perception of the role of the government, students think the government is not good at completing illegal downloads, but students agree that the government helps build a culture and understanding of the community to respect the work of others.